Enhancement of Acid Protease Activity of Aspergillus oryzae Using Atmospheric and Room Temperature Plasma - Shu, Liang; Si, Xiaoguang; Yang, Xinda; Ma, Wenyan; Sun, Jinglan; Zhang, Jian; Xue, Xianli; Wang, Depei; Gao, Qiang (Frontiers in Microbiology, 2020)
Atmospheric and room temperature plasma (ARTP) system is a novel and efficient mutagenesis protocol for microbial breeding. In this study, ARTP was employed to treat spores of Aspergillus oryzae strain 3.042 for selection of high acid protease producers. With an irradiation time of 150 s at the lethal rate of 90%, 19 mutants with higher acid protease activity were initially selected based on different mutant colony morphology and ratio of the transparent zone of protease activity to the colony diameter. Measurements of the acid protease activity revealed that mutant strain B-2 is characterized by a steady hereditary stability with increased acid protease, neutral protease and total protease activities of 54.7%, 17.3% and 8.5%, respectively, and decreased alkaline protease activity of 8.1%. In summary, the identified mutant strain B-2 exhibits great potential for the enhancement of the insufficient acid protease activity during the middle and later stages of soy sauce fermentation.